IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI MEDIA SOSIAL WHATSAPP DALAM MENINGKATKAN HASIL BELAJAR - Abi Aufa Muzid; Siti Asiah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2022)
: Consciously or not, the Covid-19 pandemic has forced almost all activities in daily life to use an internet connection, including education. Learning that was initially able to be done face-to-face now has to use an internet connection due to the implementation of social distancing. One of the applications used for online learning activities is WhatsApp. This research was conducted to determine the performance of Islamic Religious Education learning through WhatsApp social media and the supporting and inhibiting factors in implementing Islamic Religious Education learning activities through WhatsApp social media. This research uses qualitative research with a naturalistic phenomenological approach. The results in this study are Islamic Religious Education learning activities through WhatsApp social media, starting with taking an absence, followed by educators providing material through WhatsApp social media, conducting discussions and asking questions, and ending with giving material through power points by educators and providing conclusions. And the supporting and inhibiting factors in learning activities through WhatsApp social media are not bound by space and time, preventing the increase in the number of Covid-19, easy to operate. The inhibiting factor is that educators cannot recognize students' character well, the material provided cannot be understood by participants and are well educated, limited media and unstable signal conditions. The inhibiting factors also have an impact on decreasing student learning outcomes.